Student's works neo studio semester 04: Youth haven / Nur Izzati Sebri - Sebri, Nur Izzati (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2024)
The first project introduce student to explore the process of designing a building and its program. The project require student to design a 3D board to explain the chosen local or oversea projects with tropical architecture. The second projects theme is promoting hobby and socializing as a therapy for mental wellbeing by designing a pavillion. Before final project, student are need to complete the site analysis and synthesis at Kampung Bijuray Mongag which located at Bau district of Sarawak, plus Bau has a potential benefits in tourism and recreation destination in the state. The final project are continuation of all previous projects which is Youth Haven. Student are required to design a haven whereby the center will act as a place with people that has common interest, sharing their knowledge, experiences and uncover a wide range talents, in a building surrounded by nature.